Каникулы в Простофилино - Донцова Дарья Аркадьевна (Иронический детектив, 2007)
Экземпляры: ф.1 (20240125) / Инвентарный номер: 64165 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: Д 67 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-445.7